1996
DOI: 10.1111/j.1600-0447.1996.tb09818.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts among Inuit youth: a community survey of prevalence and risk factors

Abstract: The prevalence of and risk factors for attempted suicide and suicidal ideation were examined with a survey of 99 Inuit, aged 14-25 years, residing in a community in Northern Québec. A total of 34% of survey respondents reported a previous suicide attempt, and 20% had attempted suicide more than once. A suicide attempt had resulted in injury in about 11% of those surveyed. The prevalence of suicidal ideation was also very high: 43% of subjects reported past thoughts of suicide, and 26% had had suicidal thoughts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
48
4
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 20 publications
8
48
4
2
Order By: Relevance
“…However, participants in this study did not indicate that church attendance was a coping strategy. This finding is in contrast to other studies with Indigenous youth in the Canadian North that have found that church attendance is a protective factor for mental health not due to religious beliefs or practices, but rather a result of the social engagement with community members and strengthened interpersonal relationships within communities that occur from attending church [6,27]. The arts were useful for building intrapersonal strengths such as emotional processing of feelings and self-confidence, and acted as a catalyst for coping during difficult moments.…”
Section: Discussioncontrasting
confidence: 97%
“…However, participants in this study did not indicate that church attendance was a coping strategy. This finding is in contrast to other studies with Indigenous youth in the Canadian North that have found that church attendance is a protective factor for mental health not due to religious beliefs or practices, but rather a result of the social engagement with community members and strengthened interpersonal relationships within communities that occur from attending church [6,27]. The arts were useful for building intrapersonal strengths such as emotional processing of feelings and self-confidence, and acted as a catalyst for coping during difficult moments.…”
Section: Discussioncontrasting
confidence: 97%
“…These are: younger age, and previous psychiatric history. Despite communications of more frequent occurrence of SA in younger persons (age group 14/15-19 years vs. 20-24/25) (6,14,20), our studies did not show any significant differences between the quantity of all students with SA and SI in compared age groups: 14-17 and 18-21 years. This may result from adopting slightly different age ranges.…”
Section: Discussioncontrasting
confidence: 83%
“…The occurrence of suicidal behaviour also largely depends on geopolitical conditions (18)(19)(20)(21) In various European countries, the prevalence of suicidal ideation and suicide attempts in adolescents falls into quite a wide range of numbers: 3-59% and 1.3-20%, respectively (1,5,22). The prevalence of suicidal ideation and attempts among Polish adolescents is not well known.…”
Section: Introductionmentioning
confidence: 97%
“…Thirteen percentage of these suicide attempts resulted in hospitalisation. Risk factors here are in the form of physical abuse and alcohol problems in the family (12). …”
Section: Discussionmentioning
confidence: 99%